Effect of injection duration on contrast enhancement during cardiac computed tomography angiography in newborns and infants. Issue 2 (May 2022) - Masuda, T.; Funama, Y.; Nakaura, T.; Sato, T.; Tahara, M.; Masuda, S.; Yoshiura, T.; Gotanda, R.; Arao, K.; Imaizumi, H.; Arao, S.; Hiratsuka, J.; et al.
Abstract: Introduction: To investigate how changing the injection duration at cardiac computed tomography angiography (CCTA) affects contrast enhancement in newborns and infants. Methods: Included were 142 newborns and infants with confirmed congenital heart disease who underwent CCTA between January 2015 and December 2018. In group 1 (n = 71 patients), the injection duration was 8 s; in group 2 (n = 71) it was 16 s. Our findings were assessed by one-to-one matching analysis to estimate the propensity score of each patient. We compare the CT number for the pulmonary artery (PA), ascending aorta (AAO), left superior vena cava (SVC), AAO and PA enhancement ratio, and the scores for visualization between the two groups. Results: In group 1, median CT number and ranges was 345 (211–591) HU in the AAO, 324 (213–567) HU in the PA, and 62 (1–70) HU in the SVC. These values were 465 (308–669) HU, 467 (295–638) HU, and 234 (67–443) HU, respectively, in group 2 (p < 0.05). The median score for volume-rendering visualization on 3D images of the CCTA was 2 in group 1 and 3 in group 2; the score for visualization of the left SVC of the maximum intensity projection images was 2 in group 1 and 3 in group 2 (p < 0.05). The CT number for the AAO and PA enhancement ratio was 15.2 in group 1 and 9.2 in group 2 (p < 0.05). Conclusion: The 16-sec injection protocol yielded significantly higher CT numbers for the AAO, PA, and the SVC than the 8-sec injection protocol; the visualization scores were also significantly higher in group 2. Implications for practice: In newborns and infants, the longer injection time for CCTA yields stable and higher contrast enhancement at identical CM concentrations.